Czym był dla Kościoła Sobór Trydencki (1545-1563)? : (refleksje w 440-tą rocznicę od zakończenia obrad) - Gręźlikowski, Janusz (Prawo Kanoniczne, 2003)
In the history of canon law, as well as like in history of many other forms and aspects of ecclesiastical life, Trident Council (1545-1563) was of a great importance. Renovation work initiated by Council, thought as remedy for crisis situation intensified by reformation outbreak, was without any doubts a turning point not only in history of church legislation, but also in the history of Church itself. For hundred and forty years from ending of the conference of Trident Council is an occasion for discerning reflection over the role and importance of votes of that significant and grave event in the history of the Church, which was a great gift of the Spirit presented to the Church in hard times of XVIth century and turning point that started big, needed and salutary reform and renovation of the Church. Trident formed and changed the visage of Catholic Church more than any other ordinary Council except of The Und Vatican Council. The other Councils, despite their significance, influenced only specific areas of Church life, impressing their impact on them. It set a new direction and shape to the whole historical epoch. It was this Council that formed „catholic confession Church”, it gave him an order and shape in doctrinal and disciplinary area. Legal resolutions of the Council had first of all reformative character. Besides passing the resolutions, which had fundamental importance for Church’s work, as residency dictation, ban of benefices accumulation, establishing the clerical seminary, enforcing the obligatory legal form of marriages contracting or reform of religious law, the Council implemented all line of improvements and institutions started by Apostolic Capital. The great gift of the Spirit, reforms and renovation presented to the Church of the half of XVIth century in resolutions of Trident Council was to release comprehensive trend of assimilation by individual countries, nations, church’s provinces and dioceses the basic decrees and resolution, which were taken by Council’s fathers. Before everything else, situation that the Church winded up in required all that, because Church was from one side menaced by developing reformation, from the other side it was afflicted by crisis of its structures and institutions, collapse of discipline of priesthood and declining religious life. This situation forced to take on changes and reforms programmed by the Tridentinum and which concern widely understood religious renovation referring to priesthood and secular congregation, as well as Church structures themselves. In the same time, the point was both to correct recognition of totality of Council’s reformatory resolutions and to definitely implement them and enforce into life of mentioned church units. Acceptance of Trident resolutions meant the beginning of reforms on many areas of church and religious life. So no wonder, that efforts of popes from the end of XVIth century and the subsequent centuries were directed to propagate a conviction in Church’s consciousness, that Tridentinum should be recognized as not only the ultimate principle of faith, but also as rule of church discipline. Norms established earlier were integrated, specified and updated by Trident becoming a significant motor of further legislative activity of legislators in the Church. On the Council, foundations for development of modern canon law and its application in the Church were also set. Hereof, taking this all into consideration we can state, that this Council is a beginning of a new epoch for history of canon law. Its resolutions explained and determined dogmatic matters, strengthened organization and discipline in the Church, gave a new impulse to maintain shaken internal cohesion of the Church and created convenient conditions to take up offensive priestly action on wider scale. Thus they had significant impact on four centuries of life, activity and history of the church.